2022
DOI: 10.1155/2022/3440217
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Current Situation and Innovation of News Communication under the Environment of Financial Media

Abstract: In order to solve the problem of news communication innovation in the financial media environment, meet the update needs of news communication in the financial media environment, and make up for the shortcomings of the application of emerging media technologies in news communication, it is necessary to improve people's attention to news communication. With the advent of the era of integrated media, the application of emerging media technologies such as data news and robot news to the field of news communicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Not only that, the “lucid waters and lush mountains are invaluable assets” advocated by President Xi Jinping has been written into the party constitution. Green has become the main color of the development of the current era, and ecological environment construction has become an important part of the Chinese dream [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Not only that, the “lucid waters and lush mountains are invaluable assets” advocated by President Xi Jinping has been written into the party constitution. Green has become the main color of the development of the current era, and ecological environment construction has become an important part of the Chinese dream [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, financial news has been attached great importance and is closely related to China's entry into the WTO [11]. The emergence of financial news has promoted the evolution of financial media toward specialization [12]. The research objects of financial media mostly focus on professional financial media and comprehensive paper media.…”
Section: Emotional Classification Of Financial News In Artificial Int...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%